2003
DOI: 10.1017/s0047404503325047
|View full text |Cite
|
Sign up to set email alerts
|

American Sign Language in virtual space: Interactions between deaf users of computer-mediated video communication and the impact of technology on language practices

Abstract: A B S T R A C TAccording to some discussions concerning new information technologies and technologically enhanced communication, we are now in a revolution as profound as the printing press. The Internet is creating new kinds of meetingplaces and work areas and the possibilities of new types of relationships across time and space. This article reports on some ways that the Internet is shaping language practices in the Deaf community, with an interest in how new tools mediate and influence human behavior, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 13 publications
0
65
0
4
Order By: Relevance
“…In particular, this study adds to the discussion of turn beginnings (Mondada, 2007;Streeck & Hartge, 1992), and thus extends the boundaries of traditional linguistics. Similarly, it adds to the existing literature on the use of multimodal resources as "an ecology of sign systems" (C. Goodwin, 2003a) that is used in and through interaction to perform a range of social actions (e.g., C. Goodwin, 2001Goodwin, , 2003bHindmarsh & Heath, 2000Keating & Mirus, 2003;Lazaraton, 2004;Szymanski, 1999). In this article this is related to, and based on, video recordings from second language classroom interaction, and is discussed in related to pedagogical implications for second language teaching.…”
Section: Mortensenmentioning
confidence: 91%
“…In particular, this study adds to the discussion of turn beginnings (Mondada, 2007;Streeck & Hartge, 1992), and thus extends the boundaries of traditional linguistics. Similarly, it adds to the existing literature on the use of multimodal resources as "an ecology of sign systems" (C. Goodwin, 2003a) that is used in and through interaction to perform a range of social actions (e.g., C. Goodwin, 2001Goodwin, , 2003bHindmarsh & Heath, 2000Keating & Mirus, 2003;Lazaraton, 2004;Szymanski, 1999). In this article this is related to, and based on, video recordings from second language classroom interaction, and is discussed in related to pedagogical implications for second language teaching.…”
Section: Mortensenmentioning
confidence: 91%
“…The limitations of this smaller viewing area result in signers making adjustments, one of which is decreasing the size of their signing space. In a study of four Deaf families over a two-year period, Keating and Mirus (2003) found radical differences in the size of the signing space used during computermediated signing. This included:…”
Section: Adaptations Due To a Restricted Signing Spacementioning
confidence: 99%
“…However, there are still many calls in which the image is blurred, pixilated and difficult to see due to issues with transmission speeds, technical problems, or older equipment. Keating and Mirus (2003) stated that the ability to manipulate features of language and alter signing speed were important skills Deaf people used as they signed with each other using videophone technology. In order to accommodate problems with the clarity of the transmitted images, they observed the following:…”
Section: Adaptations Due To Issues With Clarity Of the Imagementioning
confidence: 99%
“…Results demonstrate that patient response to telemedicine is overwhelmingly positive, above 90 percent (e.g., Dick et al 1999). Keating & Mirus (2003) report positive results from mediated spaces which enable deaf people to communicate using manual visual language, in many cases their native language, across space and time zones. 20 It is very likely that the context of use was also a contributing factor: all patients were ill and very grateful for the possibility of faster treatment through participating in the study.…”
Section: The Example Of a Mediated Therapistmentioning
confidence: 99%